Dynamics of the support leg in soccer instep kicking - Inoue, K.; Nunome, H.; Sterzing, T.; Shinkai, H.; Ikegami, Y. (Journal of Sports Sciences, 2014)
We aimed to illustrate support leg dynamics during instep kicking to evaluate the role of the support leg action in performance. Twelve male soccer players performed maximal instep kicks. Their motions and ground reaction forces were recorded by a motion capture system and a force platform. Moments and angular velocities of the support leg and pelvis were computed using inverse dynamics. In most joints of the support leg, the moments were not associated with or counteracting the joint motions except for the knee joint. It can be interpreted that the initial knee flexion motion counteracting the extension joint moment has a role to attenuate the shock of landing and the following knee extension motion associated with the extension joint moment indirectly contributes to accelerate the swing of kicking leg. Also, appreciable horizontal rotation of the pelvis coincided with increase of the interaction moment due to the hip joint reaction force on the support leg side. It can be assumed that the interaction moment was the main factor causing the pelvis counter-clockwise rotation within the horizontal plane from the overhead view that precedes a proximal-to-distal sequence of segmental action of the swing leg.